Pandemic play moderates the relation between caregiver stress and child emotional distress in contexts of economic adversity - Rueda-Posada, María Fernanda; Thibodeau-Nielsen, Rachel B.; Dier, Shannon E.; Wilson-Dooley, Alaina; Palermo, Francisco; White, Rachel E.; Chung, Christina (Frontiers in Psychology, 2023)
It is well-established that caregiver stress is linked to increased emotional distress among children, and recent evidence highlights similar associations between caregiver and child emotional well-being during the coronavirus (COVID-19) pandemic. Examining protective factors and coping mechanisms that are associated with resiliency in the face of pandemic-related stress can highlight potential strategies that may help children adapt to other unexpected hardships outside of a global pandemic. Previous research found that playing about the pandemic moderated an association between caregiver stress and children’s emotional distress. However, few studies have explored “pandemic play” among children from low-income households, where pandemic-related stressors were often exacerbated. In the present study, 72 caregivers of Head Start preschoolers between 3 and 6 years of age were surveyed between late 2020 and early 2021. Results revealed that 32% of children engaged in pandemic play frequently. Caregiver stress was positively associated with child emotional distress, but only among children who did not engage in pandemic play frequently. These findings support the idea that child-directed play may be a developmentally appropriate and accessible coping mechanism to reduce the emotional burden of stressful events on children, regardless of economic context.